Assessment of publication time in Campbell Systematic Reviews: A cross‐sectional survey - Bei Pan; Long Ge; Xiaoman Wang; Ning Ma; Zhipeng Wei; Lai Honghao; Liangying Hou; Kehu Yang (Campbell Systematic Reviews)
Abstract Delayed publication of systematic reviews increases the risk of presenting outdated data. To date, no studies have examined the time and review process from title registration and protocol publication to the final publication of Campbell systematic reviews. This study aims to examine the publication time from protocol to full review publication and the time gap between database searches and full review publication for Campbell systematic reviews. All Campbell systematic reviews in their first published version were included. We searched the Campbell systematic review journals on the Wiley Online Library website to identify all completed studies to date. We manually searched the table of contents of all Campbell systematic reviews to obtain the date of title registration from the journal's website. We used SPSS software to perform the statistical analysis. We used descriptive statistics to report publication times which were calculated stratified by characteristics, including year of review publication, type of reviews, number of authors, difference in authors between protocol and review, and Campbell Review Groups. Non‐normal distributed data were reported as medians, interquartile range, and range, and normal distributed data will be reported as mean ± standard deviation. And we also visualized the overall publication time and the distribution of data. Approximately 18% of reviews were published within one to 2 years, faster than the aims set by Campbell systematic review policies and guidelines, which was 2 years. However, more than 40% of the reviews were published more than 2 years after protocol publication. Furthermore, over 50% of included reviews were published with a time gap of more than 2 years after database searches. There was no significant difference between Campbell coordinating groups' median publication times and time gap from searches of databases to full review publication existed. However, the methods group only published one full review with almost a 3‐year time gap from searches of databases to review publication. And there was a major difference between specific types of review. Systematic reviews had the longest median publication time of 2.4 years, whereas evidence and gap maps had the lowest median publication time of 13 months. Half of Campbell reviews were published more than 2 years after protocol publication. Furthermore, the median time from protocol publication to review publication varied widely depending on the specific type of review.